2004
DOI: 10.1038/sj.jea.7500301
|View full text |Cite
|
Sign up to set email alerts
|

Perspiration increased human pesticide absorption following surface contact during an indoor scripted activity program

Abstract: Homeowners and professional applicators frequently use chemicals to control insect pests in urban environments. The identification and evaluation of determinants of human exposure are critical to conduct reliable and responsible human exposure assessments following indoor residential chemical applications. The effect of sweat on absorbed dose in humans was evaluated with human volunteers who participated in a structured activity program (SAP). Participants (n ¼ 20) performed a warm-up exercise to induce light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…The half-life of chlorpyrifos (50 hours) determined in the present study is higher than those reported in previous studies, which ranges from 27 to 43 hours (Griffin et al 1999;Meuling et al 2005;Nolan et al 1984;Wang et al 2016;Williams et al 2004). The longer half-life found in the present study could be attributable to the octanol/water partition coefficient of the compound.…”
Section: Elimination Half-life Of Chlorpyrifos Found With the Applicacontrasting
confidence: 77%
See 1 more Smart Citation
“…The half-life of chlorpyrifos (50 hours) determined in the present study is higher than those reported in previous studies, which ranges from 27 to 43 hours (Griffin et al 1999;Meuling et al 2005;Nolan et al 1984;Wang et al 2016;Williams et al 2004). The longer half-life found in the present study could be attributable to the octanol/water partition coefficient of the compound.…”
Section: Elimination Half-life Of Chlorpyrifos Found With the Applicacontrasting
confidence: 77%
“…These findings have important implications for the design of biomonitoring programs to evaluate chlorpyrifos levels among applicators. Exposure to chlorpyrifos has often been evaluated based on urinary TCP levels obtained from the start of application up to 120 hours (5 days) post-application or less (34 hours) (Alexander et al 2006;Griffin et al 1999;Meuling et al 2005;Nolan et al 1984;Phung et al 2012b;Rodriguez et al 2006;Williams et al 2004). The measurements obtained within these sampling periods would likely under-estimate the levels of chlorpyrifos exposure, since its elimination would still be ongoing beyond these time periods.…”
Section: Elimination Half-life Of Chlorpyrifos Found With the Applicamentioning
confidence: 99%
“…They only act after the compound has passed through the epidermis to the vascular dermis, hence they appear to vary with the physical and chemical parameters of the molecule (WHO, 2006;Gordon and Leon, 2005;Tanner and Marks, 2008;Monteiro-Riviere, 2008). Sweating/skin hydration have been reported to increase dermal absorption (Gordon and Leon, 2005;Williams et al, 2004;WHO 2006) as has ambient temperature but the overall magnitude is reported to be < 2 fold (Gordon and Leon, 2005) except when occlusion was applied causing up to 9-fold increases (reviewed by Kezic and Nielsen, 2009). It can be argued that contamination by pesticide formulations/dilutions under the gloves may mimic occlusive conditions.…”
Section: Physiological Parametersmentioning
confidence: 99%
“…Operator exposure models are underpinned by data from whole body exposures, taking account of the relative areas of the high dermal absorption sites it is considered that the use of data generated following exposures of torso / breast skin will provide realistic dermal absorption values for use in exposure modelling. (Gordon & Leon, 2005;Williams et al, 2004;WHO 2006) as has ambient temperature but the overall magnitude is reported to be <2 fold (Gordon & Leon, 2005). Treatment of skin, in vivo and in vitro with an irritant such as sodium lauryl sulphate (SLS) has been shown enhance dermal absorption / penetration (Nielsen, 2005;Danish EPA, 2009) the magnitude of the enhancement (2 to >100 fold) varying with compound and the experimental procedure.…”
Section: Investigations Of Dermal Absorption Via Different Anatomicalmentioning
confidence: 99%